Examinations of equations for creep rupture life with a large creep database on grade 91 steel. (October 2022) - Maruyama, Kouichi; Dewees, Dave; Abe, Fujio; Yoshimi, Kyosuke
Abstract: Equations for predicting creep rupture life of grade 91 steel have been revised officially in Japan and European Union. First, the revised equations are examined with a large creep rupture database on the steel. The database consists of 2066 data points, and its longest creep rupture life is 232, 833 h crept at 600 °C. The equations deviate from data points of the database in a long-term region beyond 30, 000 h. Decrease in activation energy for creep rupture life in the long-term region is the cause of the deviation. A multi-region analysis of the database can be a probable way of reducing the deviation. However, some modifications of the analysis are necessary when applying it to the large database containing data points of multiple heats. A trial of the modifications is made in the second part of this paper. The equations obtained through the trial can well represent all the data points including the ones in the long-term region. Highlights: The equations for creep rupture life proposed are examined with a large database. The database consists of 2066 data points and the longest rupture life is 233, 000 h. The ECCC and METI equations overestimate long-term creep rupture life of Gr. 91 steel. Multi-region analysis is modified for applying it to the multiple-heats database. The multi-region analysis can appropriately represent long-term creep rupture life.